Boosting effect of ultrasonication on the oxygen evolution reaction during zinc electrowinning - Guihong Han; Zhen Chen; Ningdan Cui; Shuzhen Yang; Yanfang Huang; Bingbing Liu; Hu Sun (Ultrasonics Sonochemistry)
In this study, the electrochemical and anodic behaviors of Pb-Ag anodes during ultrasound-assisted zinc electrowinning were meticulously examined. The oxygen evolution reaction (OER) occurring at the Pb-Ag anodes in a 150 g L-1 aqueous H2SO4 solution was studied in the absence (silent) and presence of ultrasonication (40 kHz, 100 % acoustic amplitude). Electrochemical impedance spectroscopy (EIS), cyclic voltammetry (CV), linear sweep voltammetry (LSV), and zinc electrowinning tests were conducted to analyze the electrochemical behavior of the Pb-Ag anodes during zinc electrowinning. Compared with that under silent conditions, the OER was greatly enhanced under ultrasonic conditions, and the overpotential reduction was found to be 108 mV at 35 °C at a current density of 50 mA cm−2. A significant reduction in the bath voltage was achieved during ultrasound-assisted prolonged zinc electrowinning, with a difference of approximately 50 mV compared with that of the control. The integration of ultrasonic technology into the realm of zinc electrowinning leverages the physical and chemical effects of ultrasonication to significantly improve the efficiency and kinetics of the OER. Smaller PbO2 grains and a larger silver exposure area appeared on the Pb-Ag plate surface during ultrasonic-assisted electrowinning, which is beneficial for the OER chemically. The generated oxygen bubbles merged more rapidly and detached from the electrode surface with greater alacrity under ultrasonication conditions, which reinforced the OER in terms of mass transfer kinetics. Furthermore, more fine zinc products can be obtained during ultrasound-assisted zinc electrowinning. By harnessing the power of ultrasonic technology, more sustainable and cost-effective zinc electrowinning can be achieved.